Hubungan Industrial dalam Perspektif Pancasila - Siswanto, Dwi (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 1999)
This research aims to describe and provide any more comprehensive understanding of the Industrial Relationship in Pancasila Perspective. This is important since it has a strategical dimension in the life of nation and it will supply some contributions of judgement for the attempt of labor condition, improvement in Indonesia as a whole.This a library research and it completes the inquiries that have been done. The method adopted in analyzing the result of this study is hermeneutics with the following features: description, interpretation, holistic, heuristic, and reflection.The results of this research are shown as follows:1. The industrial relationship in the Pancasila Perspective is an antropocentric type, that is, man are placed in the center as subject and object.2. The industrial relationship in the Pancasila Perspective places